Nano-Engineered Biomaterials for Tissue Regeneration: What Has Been Achieved So Far? - Mclaughlin, Sarah; Podrebarac, James; Ruel, Marc; Suuronen, Erik J.; McNeill, Brian; Alarcon, Emilio I. (Frontiers in Materials, 2016)
Nanomaterials have attracted the interest of tissue engineers for the last two decades. Their unique properties make them promising for de-novo fabrication of bio-inspired hybrid/composite materials with improved regenerative properties, including the capacity for electric conductivity and the provision of antimicrobial properties, for example. However, to this day, the use of such materials in medical applications is rather limited and most of the studies have only reached the archetypical proof-of-concept stage. Herein, we present a review on the use of nanomaterials in tissue engineering for regenerative therapies of heart, skin, eye, skeletal muscle, and nervous system. The advantages and limitations of nano-engineering materials are presented in this review alongside with the future challenges and milestones nanotechnology must overcome to make an impact in biomedical applications.